PERAN KREDIT DAN MODAL SENDIRI TERHADAP PENDAPATAN PETANI PADI DI KECAMATAN SUKAWATI KABUPATEN GIANYAR - Made Theo Lamunas; Gde Herry Sugiarto Asana (Universitas Triatma Mulya, 2023)
The agricultural sector in Bali likewise assumes a vital part in the development and economy of the Balinese people. Agriculture is expected to be able to create a source of income, a means for entrepreneurship, and has the potential to better the population's standard of living. At present there is a lack of distribution or access to capital which causes the scale of ownership of agricultural business actors to be small so that they cannot make efficiency in production and even have no effect on income. The motivation behind this study was to examine the job of credit and value in the pay of rice farmers in Sukawati sub-district, Gianyar regency. This examination is a sort of quantitative exploration using primary data. Techniques for information assortment utilizing interviews and questionnaires. The analytical tools used to process the data are different test techniques (paired sample test) and multiple linear regression. In light of the consequences of the examination and information examination, that's what it shows credit (X1) and equity (X2) play a positive role in the income of rice farmers. Credit for rice farmers will increase the value in the pay of rice farmers